IMPLEMENTASI PEMBERIAN REHABILITASI TERHADAP PECANDU NARKOTIKA DI BNN KOTA DENPASAR - Rusdiawan, Sang Putu Aditya; Saraswati, Putu Sekarwangi (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
The State of Indonesia is a state of law, this can be seen from article 1paragraph (3) of the 1945 Constitution of the Republic of Indonesia states that